1981
DOI: 10.1002/jgt.3190050413
|View full text |Cite
|
Sign up to set email alerts
|

On graphs containing a given graph as center

Abstract: We examine the problem of embedding a graph H as the center of a supergraph G, and we consider what properties one can restrict G to have. Letting A(H) denote the smallest difference I V(G)I -I V(H)I over graphs G having center isomorphic to H it is demonstrated that A(H)54 for all H, and for 0 5 i 5 4 we characterize the class of trees T withA(T) = i. For n 2 2 and any graph H, we demonstrate a graph G with point and edge connectivity equal to n , with chromatic number x(G) = n 4-x(H), and whose center is iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 3 publications
(2 reference statements)
0
34
0
2
Order By: Relevance
“…It is well known (see [2]) that every graph is the center of some graph. In our final result, we characterize those graphs that are the center of some eccentric graph.…”
Section: Eccentric Graphs With Prescribed Subgraphsmentioning
confidence: 99%
“…It is well known (see [2]) that every graph is the center of some graph. In our final result, we characterize those graphs that are the center of some eccentric graph.…”
Section: Eccentric Graphs With Prescribed Subgraphsmentioning
confidence: 99%
“…The closed 3-stop center C 3 (G) of G is the subgraph induced by those vertices of G having minimum closed 3-stop eccentricity [2]. For a given graph G, if there exists a graph H such that C 3 (H) ∼ = G, we define the closed 3-stop central appendage number of a graph G, AC 3 (G), to be the minimum difference |V (H)| − |V (G)| over all graphs H such that C 3 (H) ∼ = G. For more on standard central appendage number of a graph we refer the reader to [5].…”
Section: (D(x Y) + D(y Z) + D(z X))mentioning
confidence: 99%
“…Hedetniemi (see [2]) showed that every graph is the center of some connected graph. Using this proof technique we establish the corresponding result for stratified graphs.…”
Section: Centers In Stratified Graphsmentioning
confidence: 99%